Ultrahigh energy density solid state supercapacitor based on metal halide perovskite nanocrystal electrodes: Real-life applications. (15th August 2023) - Ali, Mir Sahanur; Layek, Rashbihari; Ali, Mir Sahidul; Tudu, Surajit; Dutta, Koushik; Gangopadhyay, Bhuman; Karmakar, Devdas; Mallik, Amit; Panda, Subrata; Maiti, Anupam; Ghoshal, Debajyoti; Karmakar, Srikanta; et al.
Abstract: Inorganic lead halide perovskite nanocrystals have now become an emerging material for modern nanodevice applications. But, the huge toxicity of lead to the ecosystem has limited its applications in modern technology. In this view, a large organic cation-based metal halide perovskite may be considered the most efficient supercapacitor electrode material. Here, a new type and high molecular organic cations based low-dimensional metal halide perovskite (LDMHP) nanocrystals (NCs) are synthesized by a chemical process and their performances as supercapacitor electrode is tested. An excellent charge storage capacity and especially the Tin (Sn)-based perovskite NCs showed a very high specific capacitance and energy density of ~1536 Fg −1 and ~213 Whkg −1 at a current density of 2.0 Ag −1, respectively. The calculated variable parameter ( b ) value from cyclic voltammetry showed that the total capacity of the Sn-based perovskite NCs electrode is controlled by capacitor-like behaviour. The Sn NCs also found to have a very high DC dielectric constant at room temperature, possibly responsible for their superior supercapacitor performance. A solid-state supercapacitor based on synthesized NCs was used for real-life applications of supplying sufficient power to light emitting diodes (LEDs) for a long time. Graphical abstract: Unlabelled Image Highlights: Low dimensional metal halide perovskite with different metal was synthesized. Different morphologies were obtained by using different metal. The specific capacitance was measured from CV and GCD spectra. The energy and power density were measured from GCD spectra. Solid state Supercapacitor was fabricated in our lab which was able to power up a LED.